Aerial Application of Pheromones for Mating Disruption of an Invasive Moth as a Potential Eradication Tool - Brockerhoff, Eckehard G. (Public Library of Science, 2012)
Biological invasions can cause major ecological and economic impacts. During the early stages of invasions, eradication is desirable but tactics are lacking that are both effective and have minimal non-target effects. Mating disruption, which may meet these criteria, was initially chosen to respond to the incursion of light brown apple moth, Epiphyas postvittana (LBAM; Lepidoptera: Tortricidae), in California. The large size and limited accessibility of the infested area favored aerial application. Moth sex pheromone formulations for potential use in California or elsewhere were tested in a pine forest in New Zealand where LBAM is abundant. Formulations were applied by helicopter at a target rate of 40 g pheromone per ha. Trap catch before and after application was used to assess the efficacy and longevity of formulations, in comparison with plots treated with ground-applied pheromone dispensers and untreated control plots. Traps placed at different heights showed LBAM was abundant in the upper canopy of tall trees, which complicates control attempts. A wax formulation and polyethylene dispensers were most effective and provided trap shut-down near ground level for 10 weeks. Only the wax formulation was effective in the upper canopy. As the pheromone blend contained a behavioral antagonist for LBAM, ‘false trail following’ could be ruled out as a mechanism explaining trap shutdown. Therefore, ‘sensory impairment’ and ‘masking of females’ are the main modes of operation. Mating disruption enhances Allee effects which contribute to negative growth of small populations and, therefore, it is highly suitable for area-wide control and eradication of biological invaders.